Penyuluhan Senam Hamil untuk Mengurangi Tingkat Stres Ibu Hamil Trimester III dalam Menghadapi Persalinan di Puskesmas III Denpasar Selatan - Ni Wayan Noviani; Ni Nyoman Ayuk Widiani (Jurnal Pengabdian UNDIKMA, 2021)
This community service aims to provide education to pregnant women in the third trimester about the benefits of pregnancy exercise to reduce stress in facing childbirth. Puskesmas III Denpasar Selatan organizes class activities for pregnant women every week to provide education to pregnant women. The method used in this service is by providing online counseling during classes for pregnant women. Participants in this service program are third trimester pregnant women who take part in the pregnant women class program. The results of this counseling activity has helped pregnant women manage stress levels when facing childbirth with the help of educational videos that can be applied at home.